Проблема аналізу матеріальних оборотних активів - Кузнецова, Світлана Олександрівна; Лисенко, Я. А. (Edizioni Magi, Roma, Italy, 2017)
У статті розглядаються основні проблемні питання аналізу поточних активів підприємства в контексті методології аналізу та її інформаційної підтримки, проведено аналіз можливостей покращення ефективності функціонування підприємства, аналіз ефективного формування та використання оборотних активів.

The article considers the main problematic issues of the analysis of the company's current assets in the context of the analysis methodology and its information support, an analysis of the possibilities for improving the efficiency of the enterprise's functioning, analysis of the effective formation and use of working capital.
Problem of analysis of material current assets
Keywords: запаси; обігові кошти; поточні активи; підприємство; витрати; цикл; inventories; current assets; enterprise; expenses; cycle